Investigating the effect of gamification on the adoption of fitness apps on mobile devices in South Africa - Ritchie, Janine (Department of Computer Science, 2020)
Despite the large number of downloads of mobile apps and the growth of the fitness mobile app industry, research shows that fitness mobile apps are faced with the issue of having a low adoption rate. This thesis focusses on fitness mobile apps and attempts to understand this issue of adoption or continuous fitness mobile app usage in a South African context and specifically looks at the role of gamification in fitness mobile app adoption. The research is conducted to better understand how gamification affects and can improve fitness mobile app adoption. Gamification can be defined as the addition of points, badges, leaderboards and other elements found in games to other non-game related areas such as fitness apps. A survey was administered to three cohorts of students at the University of Cape Town in South Africa to assess this. The cohorts focused on MyFitnessPal, Nike+ or Strava gamified fitness mobile apps, respectively, in order to allow for comparisons of survey responses across the three fitness mobile apps. The survey design used an extension of the Technology Acceptance Model (TAM) to quantitatively measure the relationship between gamification in fitness mobile apps and the behavioural intention to adopt the fitness mobile app. User perspectives on how gamification affects adoption of fitness mobile apps was also gathered in the survey. Perceived usefulness (PU), perceived ease of use (PEU) and perceived enjoyment (PE) were found to have a positive relationship to the behavioural intention (BI) to adopt a fitness mobile app in the sample. Across the cohort’s subjective norm didn't significantly contribute to the BI to adopt a fitness mobile app. Interestingly it was found to correlate negatively with the variable BI when analyzing the responses from the Nike+ cohort. In the cohorts for MyFitnessPal and Strava this was not the case as these two variables were found to be positively correlated. The progress bar was perceived to be the most useful gamification element in a fitness mobile app in all three cohorts when compared with leaderboards, badges, levels and points. When looking at how gamification improves adoption motivations the following popular reasons were provided by participants: progress tracking and achievement (encourage improvement). This was followed by the common themes PEU, PE, award/incentive, competitive aspect and goal setting assistance. The findings from this study contribute to better understanding how gamification improves fitness app adoption in a South African context.